2D scalar wave modelling of apodized RF BAW resonators for transverse mode analysis. (1st January 2023) - Wu, Ting; He, Yi-wen; Wong, Yu-po; Li, Wuping; Bao, Jing-fu; Hashimoto, Ken-ya
Abstract: This paper proposes the use of a two-dimensional scalar wave model for fast analysis of apodized AlN-based radio frequency bulk acoustic wave devices. First, the working principle and model setup is introduced. Only one particular Lamb mode (S1− ) is considered, and its behavior is modeled by a simple scalar wave equation looking from the top surface. Multiple layers are added to the side boundaries so that mode conversion to other modes is treated as leakage to surroundings. The wavenumber of field distribution for each resonance mode is calculated, and then its excitation coefficient, quality factor, and resonance frequency are derived. The device input admittance is calculated by applying derived parameters to the equivalent circuit. A series of oval-shaped AlN-based film bulk acoustic resonator devices are simulated and compared with experimental results. The theoretical results agreed well with the experimental ones, and accuracy and effectiveness of the present analysis are verified.